The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.3354/dao059151
|View full text |Cite
|
Sign up to set email alerts
|

Parasitic castration of Eurhomalea lenticularis (Bivalvia: Veneridae) by a digenetic trematode: quantitative histological analysis

Abstract: The clam Eurhomalea lenticularis may be parasitized by digenean trematodes of the family Plagiorchidae, specifically in the gonads (parasitic castration). A quantitative histological analysis of the parasitized gonads demonstrated a significant decrease in gonadal area, in the size of individual acini, and in the numbers of differentiated germ cells compared to unparasitized clams. Castration may be caused by mechanical compression due to trematode sporocyst growth. However, the uniform loss of germ cells in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…In addition to mortality, G. choledochus seems to castrate its host since no gonad structures could be observed in infected individuals. Such parasite induced castration was also observed in other parasite-bivalve associations (Coustau et al, 1993;Silva et al, 2002;Valderrama et al, 2004). Hence, the infected part of the local adult cockle population is probably no longer reproducing.…”
Section: Discussionmentioning
confidence: 80%
“…In addition to mortality, G. choledochus seems to castrate its host since no gonad structures could be observed in infected individuals. Such parasite induced castration was also observed in other parasite-bivalve associations (Coustau et al, 1993;Silva et al, 2002;Valderrama et al, 2004). Hence, the infected part of the local adult cockle population is probably no longer reproducing.…”
Section: Discussionmentioning
confidence: 80%
“…In South America, studies of parasites and diseases of bivalves are scarce (CaceresMartinez & Vasquez-Yeomans 2008), even though they are important and necessary. In Chile, major contribution about presence of parasites in molluscs have been recorded by Oliva (1984Oliva ( , 1992, Oliva et al (1986Oliva et al ( , 1999Oliva et al ( , 2010, Franjola & Gallardo (1991), Gallardo et al (1992), Oliva & Vega (1994), García-Tello et al (2002), Valderrama et al (2004), and pathogens by Lohrmann et al (2002), Lohrmann (2009), Campalans & Lohrmann (2009. However, the knowledge of pathogens and parasites in marine organisms inhabiting San Jorge Bay (Antofagasta) and the majority of the Chilean coast remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Cake (1977) reported that cestode infections also cause physiological stress, resulting in a negative effect on the reproduction of marine mollusks. Such failure of the host's reproduction is caused by deprivation of essential nutrients, impacts on the host's natural endocrine system, and genetic modulation (Crews and Yoshino, 1989;Valderrama et al, 2004;Rice et al, 2006). Similarly, we found that trematodes, together with cestode infections, cause severe tissue damage in the gonads.…”
Section: Effect Of Metazoan Parasites On Host Reproductionmentioning
confidence: 76%